Innovation in hanging bamboo weaving of malet gusti using modern techniques for interior design and building facades: Sustainable materials - Gunawarman, Anak Agung Gede Raka; Pradnyaningrum, Putu Siskha; Murti, Anak Agung Gede Krisna; Utari, Putu Marchia Eka; Atmaja, I Made Alit Giri Rama Kanaka (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: As awareness of the importance of sustainability continues to grow, the demand for environmentally friendly products has also increased. However, the bamboo craft industry in Indonesia faces challenges in enhancing the added value of its products, such as improving production efficiency and diversifying designs to meet modern market demands. This study aims to develop more efficient bamboo weaving techniques through the utilization of bamboo splitting machines and analyze their impact on product quality and craftsmen's competitiveness. Methods: The research employed a development method (Research and Development) with both qualitative and quantitative approaches. Data were collected through observations, in-depth interviews, and product trials conducted during a training program in Penglumbaran Village, Bangli. The program integrated traditional techniques with modern technology to produce wall panels, interior partitions, and exterior facades. Findings: The results showed a 48% increase in production time efficiency and the development of three new weaving models with higher aesthetic value. Additionally, craftsmen demonstrated enhanced skills in combining technological innovation with traditional techniques. Conclusion: This study has implications for improving the competitiveness of bamboo weaving products in local and international markets, strengthening the local economy through product diversification, and contributing to environmental preservation through the use of sustainable materials. These findings highlight that technology-based innovation can serve as a strategic solution to bridge tradition and modernity in the bamboo craft industry. Novelty/Originality of this Study: This study offers a unique approach by combining traditional bamboo weaving techniques with modern bamboo splitting technology, bridging the gap between tradition and modernity while enhancing both product efficiency and quality in the bamboo craft industry.